Estudo dos efeitos cardiovasculares e hepáticos da trans-desidrocrotonina (t-DCTN), um diterpeno clerodano obtido do Croton cajucara Benth. (sacaca) - Prado, Regilane Matos da Silva (2005)
Croton cajucara Benth (Euphorbiaceae) is a popular medicinal plant in the Amazon region of Brazil for the treatment of liver and kidney disorders and also to lower blood cholesterol. The trans-dehydrocrotonin (t-DCTN), is the major clerodane diterpene isolated from the stem bark of Croton cajucara, that showed gastroprotective, hypoglycemic and hypolipidemic effects. Since drugs that possess pharmacological properties are often associated with contradictory cardiovascular and hepatic effects with possible cytoprotection or cytotoxicity properties, the present study aimed to examine the effects of t-DCTN (i) in the tests of lethality to Artemia sp and in primary cultures of mesencephalic and hepatic cells in vitro; (ii) on hepatotoxicity induced in vivo by acetaminophen or galactosamine/LPS in mice and (iii) on arterial blood pressure and heart rate in vivo, and on chronotropism and inotropism on isolated preparations of rat atria and aortic rings. The t-DCTN (0.3 to 300 Micromolar) demonstrated low toxicity to Artemia sp (LC50 of 670 ± 80 Micromolar), and manifested no per se cytotoxicity on primary cultures of mesencephalic cells but could effectively revert the reduced cell viability induced by neurotoxin, 6-OHDA (200 Micromolar). On the other hand, t-DCTN (0.3–300 Micromolar) displayed cytotoxicity similar to ethanol (50-400 Milimolar) in primary cultures of hepatocytes. It, however offered hepatoprotection against acetaminophen (500 mg/kg)-induced hepatotoxicity in mice, evidenced from biochemical parameters of hepatic glutathione, and malonaldehyde, and serum AST and ALT levels. Nevertheless, the histological scores in liver tissues were not significantly altered by t-DCTN pretreatment. t-DCTN pretreatment also offered protection against galactosamine/LPS-induced hepatotxcity through restoration of glutathione and reductions in serum AST and ALT levels. In pentobarbital sodium anesthetized normotensive rats, t-DCTN produced hypotensive and bradycardia responses in a dose-dependent manner. The hypotensive effect of t-DCTN (10 mg/kg) was not affected by atropine, propranolol or hexamethonium but was abolished by L-NAME. In isolated right atria, t-DCTN inhibited the spontaneous beating but it was unable to reduce the isoproterenol-induced increase in heart beat. The inotropism was unchanged in the presence of t-DCTN in isolated left atria. In isolated rat aortic rings, t-DCTN relaxed the tonic contraction induced by phenylephrine (1 Micromolar), which was abolished in endothelium denuded or in L-NAME treated tissues. t-DCTN possessed low toxicity to Artemia sp; is devoid of neurotoxicity to mesencephalic cells; either induced hepatotoxicity or hepatoprotection, depending on the models used, and further suggested a possible inhibitory action on cytocrhrome-P450. The hypotensive action of t-DCTN may possibly involve in part the nitric oxide release from endothelium, and in part a direct relaxant effect on vascular smooth muscle. Taken together the data available in literature with the present observations suggest a caution while extrapolating animal data for a promising therapeutic utility of t-DCTN especially in the treatment of hepatic disorders or diabetes associated pathologies.